A Proposal for a Noxious Stimuli-Free, Moderate-Intensity Treadmill Running Protocol to Improve Aerobic Performance in Experimental Research on Rats - de Assis, Gilmara Gomes [UNESP]; de Souza, Elda Olivia Nobre [UNESP]; de Almeida-Neto, Paulo Francisco; Ceylan, Halil İbrahim; Bragazzi, Nicola Luigi (MDPI, 2024)
Background/Objectives: Animal models can help understand human physiological responses, including the response to exercise and physical activity. However, many of these models incorporate noxious stimuli for various scientific purposes. We propose a noxious stimuli-free treadmill running training program for Rattus norvegicus species to study adaptations to aerobic exercise. Methods: In this study, rats were randomly allocated to training (n = 20) and sedentary (n = 20) groups. The training group underwent a program consisting of 30–50 min of treadmill running at 60% intensity, three times per week for 8 weeks. Maximum speed tasks (Tmax) were conducted to determine, adjust, and evaluate changes in fitness conditions. The rats had one week of familiarization with the treadmill, and a rubber ball was used at the back wall of the lane as a painless stimulus to encourage running. All assessments were conducted by two independent researchers in a double-blind manner, with data analysis conducted by a third-blind investigator. Results: A significant effect of time (η2p = 0.430, p < 0.001, large effect) could be found, showing differences between Tmax1 and Tmax2, and between Tmax1 and Tmax3 in both groups. The training group significantly outperformed the sedentary group (η2p = 0.266, p < 0.001, large effect). There was a significant interaction between time and condition (η2p = 0.152, p < 0.001, large effect). Conclusions: The proposed moderate-intensity treadmill running program could effectively differentiate between trained and sedentary conditions within both the short period of 4 weeks and the extended period of 8 weeks. This protocol can be used as a model for running on a treadmill for Rattus norvegicus species without the use of noxious stimuli.
Keywords: aerobic exercise; animal models; animal research; fitness; rat; treadmill running